Pengaruh Brand Awareness, Brand Characteristic, dan Emotional Branding terhadap Keputusan Pembelian - Muthiah, Farah; Setiawan, Budi (Jurnal Ilmiah Manajemen Kesatuan, 2019)
The research includes the type of survey research whose information is collected through questionnaires from respondents. The population of the study is the consumers who make purchasing decisions on beauty products Wardah. The sample of research is 100 respondents. Data collection techniques using questionnaires tested the validity and reliability. Data analysis techniques used to answer the hypothesis of research is multiple linear regression. The result of this research shows that Brand Awareness has negative and insignificant effect on Wardah Beauty Decision, Brand Characteristic has a positive and significant influence on Purchasing Decision of Wardah beauty product, Emotional Branding has a positive and significant influence on Purchasing Decision of Wardah, Brand Awareness, Brand Characteristic, and Emotional Branding together have a positive and significant influence on Purchase Decision Wardah beauty products On STIE Kesatuan Bogor Students.